Ethnography as an Inquiry Process In Social Science Research - Gautam, Ganga Ram (Tribhuvan University Journal, 2016)
This article is an attempt to present the concept of ethnography as a qualitative inquiry process in social science research. The paper begins with the introduction to ethnography followed by the discussion of ethnography both as an approach and a research method. It then illustrates how ethnographic research is carried out using various ethnographic methods that include participant observation, interviewing and collection of the documents and artifacts. Highlighting the different ways of organizing, analyzing and writing ethnographic data, the article suggests ways of writing the ethnographic research.